Interpersonal Influences on Body Representations in the Infant Brain - Drew, Ashley R.; Meltzoff, Andrew N.; Marshall, Peter J. (Frontiers in Psychology, 2018)
Within cognitive neuroscience, there is burgeoning interest in how the body is represented in the adult brain. However, there are large gaps in the understanding of neural body representations from a developmental perspective. Of particular interest are the interconnections between somatosensation and vision, specifically infants’ abilities to register correspondences between their own bodies and the bodies of others. Such registration may play an important role in social learning and in engendering feelings of connectedness with others. In the current study, we further explored the interpersonal aspects of neural body representations by examining whether responses to tactile stimulation in 7-month-old infants are influenced by viewing another’s body. During EEG recording, infants (N = 60) observed a live presentation of an experimenter’s hand or foot being touched. During the presentation of touch to the adult’s hand or foot, the infant received a brief tactile touch to their right hand or right foot. This resulted in four conditions: (i) Receive hand stimulation/observe hand stimulation, (ii) receive hand stimulation/observe foot stimulation, (iii) receive foot stimulation/observe hand stimulation, and (iv) receive foot stimulation/observe foot stimulation. Analyses compared responses overlying hand and foot regions when the observed limb matched the stimulated limb (congruent) and did not match (incongruent). In line with prior work, tactile stimulation elicited a somatotopic pattern of results in the somatosensory evoked potential (SEP) and the sensorimotor mu rhythm (6-9 Hz). Cross-modal influences were observed in the beta rhythm (11-13 Hz) response and in the late potential of the SEP response (400-600 ms). Beta desynchronization was greater for congruent compared to incongruent conditions. Additionally, tactile stimulation to the foot elicited larger mean amplitudes for congruent compared to incongruent conditions. The opposite was true for stimulation to the hand. This set of novel findings suggests the importance of considering cross-modal effects in the study of neural body representations in the infant brain. Continued work in this new area of infant neuroscience research can inform how interpersonal aspects of body representations may serve to undergird early social learning.